Trajectory Control and Resource Allocation for UAV-Based Networks with Wireless Backhauls - Nguyen, Minh Dat; Bao Le, Long; Girard, Andre (IEEE International Conference on Communications (2003), 2021)
In this paper, we study the trajectory control and sub-channel assignment for unmanned aerial vehicle (UAV) based wireless networks with wireless backhauls. This design aims to maximize the min rate achieved by ground users (GUs) subject to their data transmission demands. To tackle the underlying mixed integer non-linear optimization problem, we use the alternating optimization approach where we iteratively optimize the sub-channel assignment and UAV trajectory control until convergence. Toward this end, we propose a heuristic algorithm to obtain a feasible solution for the sub-channel assignment sub-problem. In addition, the successive convex approximation (SCA) method is used to convexify and solve the non-convex UAV trajectory control sub-problem. Via extensive numerical studies, we illustrate the effectiveness of our proposed design for different network settings.